Does artificial light at night change the impact of silver nanoparticles on microbial decomposers and leaf litter decomposition in streams?. Issue 6 (3rd May 2019) - Pu, Gaozhong; Zeng, Danjuan; Mo, Ling; He, Wen; Zhou, Longwu; Huang, Kechao; Liao, Jianxiong; Qiu, Shuo; Chai, Shengfeng
Abstract : The negative effect of AgNP on leaf litter decomposition was alleviated by artificial light at night (ALAN). Abstract : The toxic effects of silver nanoparticles (AgNP) to aquatic species and ecosystem processes have been the focus of increasing research in ecology, but their effects under different environmental stressors, such as the ongoing anthropogenic artificial light at night (ALAN) which can cause a series of ecological effects and will potentially interact with other stressors, remain poorly understood. Here, we aimed to assess the combined effects of AgNP and ALAN on the activities and community structure of fungi and bacteria associated to plant litter in a stream. The results showed that ALAN not only led to changes in the average hydrodynamic diameter, ζ -potential and dissolved concentration of AgNP but also inhibited the enzyme activities of leucine-aminopeptidase (LAP), polyphenol oxidase (PPO) and peroxidase (PER) associated with microbes involved in litter decomposition. The negative effect of AgNP on the decomposition of Pterocarya stenoptera leaf litter was alleviated by ALAN owing to the reduction of the Ag + concentration in the microcosm and of the lignin content of the leaf litter in the A-AgNP treatments, the enhancement of β-glucosidase (β-G) activities and the increase in microbial biomass. The effect of ALAN alone or combined with AgNP or AgNO3 on the taxonomic composition of fungi was much greater than that on bacteria. Linear discriminant analysis effect size (LEfSe) demonstrated that each treatment had its own fungal and bacterial indicator taxa, from the phylum to genus levels, indicating that the microbial communities associated with litter decomposition can change their constituent taxa to cope with different stressors. These results reveal that ALAN can decrease the toxicity of AgNP and highlight the importance of considering ALAN during the assessment of the risk posed by nanoparticles to freshwater biota and ecosystem processes.